Campbell biology - Reece, Jane B.; Urry, Lisa A.; Cain, Michael L. (Michael Lee) 1956-; Wasserman, Steven Alexander (Pearson Education, Inc., 2014)
The Tenth Edition helps you develop a deeper understanding of biology by making connections visually across chapters and building the scientific skills needed for success in upper-level courses. New Make Connections Figures pull together content from different chapters visually, helping you see "big picture" relationships. New Scientific Skills Exercises in every chapter use real data to build key skills needed for biology, including data analysis, graphing, experimental design, and math skills. New Scientific Skills Exercises in every chapter use real data to build key skills needed for biology, including data analysis, graphing, experimental design, and math skills.